Diaryl azo derivatives as anti-diabetic and antimicrobial agents: synthesis, in vitro, kinetic and docking studies - Tehreem Tahir; Mirza Imran Shahzad; Rukhsana Tabassum; Muhammad Rafiq; Muhammad Ashfaq; Mubashir Hassan; Katarzyna Kotwica-Mojzych; Mariusz Mojzych (Taylor & Francis Group, 2021)
In the present study, a series of azo derivatives (TR-1 to TR-9) have been synthesised via the diazo-coupling approach between substituted aromatic amines with phenol or naphthol derivatives. The compounds were evaluated for their therapeutic applications against alpha-glucosidase (anti-diabetic) and pathogenic bacterial strains E. coli (gram-negative), S. aureus (gram-positive), S. aureus (gram-positive) drug-resistant strain, P. aeruginosa (gram-negative), P. aeruginosa (gram-negative) drug-resistant strain and P. vulgaris (gram-negative). The IC50 (µg/mL) of TR-1 was found to be most effective (15.70 ± 1.3 µg/mL) compared to the reference drug acarbose (21.59 ± 1.5 µg/mL), hence, it was further selected for the kinetic studies in order to illustrate the mechanism of inhibition. The enzyme inhibitory kinetics and mode of binding for the most active inhibitor (TR-1) was performed which showed that the compound is a non-competitive inhibitor and effectively inhibits the target enzyme by binding to its binuclear active site reversibly.